THE SIGNIFICANCE OF THE TERM “HABEAS CORPUS” IN THE HUMAN RIGHTS SYSTEM (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the significance of the principle and legal concept of Habeas Corpus within the contemporary human rights system. The study analyzes the historical evolution of the Habeas Corpus doctrine, its legal foundations, and its role in protecting individuals against arbitrary detention and unlawful deprivation of liberty. Particular attention is paid to the relationship between Habeas Corpus and the principles of the rule of law, judicial protection, due process, and international human rights standards. The article also evaluates the implementation of Habeas Corpus mechanisms in modern legal systems and their contribution to ensuring justice and safeguarding fundamental freedoms. The findings indicate that Habeas Corpus remains one of the most effective legal instruments for preventing abuses of state power and protecting human dignity.